1997
DOI: 10.1093/intimm/9.11.1757
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation of B cells and T cells is required for survival of mice infected with vesicular stomatitis virus

Abstract: To define the role of T cells and B cells in resistance to vesicular stomatitis virus (VSV) infection, knockout mice with different specific immune defects on an identical background were infected i.v. and the outcome of infection was compared; in this way a more complete picture of the relative importance of various host defence mechanisms could be obtained. Compared to T and B cell-deficient SCID mice which all succumbed from encephalitis within 5-9 days of infection, T cell-deficient nude mice generally liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
78
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(82 citation statements)
references
References 34 publications
4
78
0
Order By: Relevance
“…It is assumed that clearance of RNA viruses from neurons is initiated by the expression of IFN-␤ and that it is primarily mediated by neutralizing Abs that effectively inhibit the production of new virus but do not necessarily eliminate virus RNA from cells. This concept is in line with the observation that CD4-depleted WT mice, which mount only short-lived neutralizing Ab responses, show an increased susceptibility to lethal VSV infection (14,37).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…It is assumed that clearance of RNA viruses from neurons is initiated by the expression of IFN-␤ and that it is primarily mediated by neutralizing Abs that effectively inhibit the production of new virus but do not necessarily eliminate virus RNA from cells. This concept is in line with the observation that CD4-depleted WT mice, which mount only short-lived neutralizing Ab responses, show an increased susceptibility to lethal VSV infection (14,37).…”
Section: Discussionsupporting
confidence: 79%
“…These observations are in line with a previous study also showing that MHC class I-deficient mice showed a similar disease course upon i.n. VSV infection compared with WT mice (37). However, another study showed that in the absence of CD8 ϩ T cells, a reduced survival of VSV infection was observed (3).…”
Section: Discussionmentioning
confidence: 99%
“…Although cytotoxic T cell responses are generally considered to be critical for resolving viral infections, substantial evidence indicates that it is the antibodies that play an indispensable role in the early phase of VSV infection. For example, B cell-de cient mice are highly susceptible to low doses of virus, although mortality can be prevented by transferring naive B cells to the mice before challenge as well as by administering immune serum after challenge (15)(16)(17). The type-speci c VSV G protein is the viral antigen giving rise to the neutralizing antibodies that are critically important in eliminating VSV infection.…”
Section: Resultsmentioning
confidence: 99%
“…Semliki Forest virus clearance is delayed several weeks in the absence of B cells (47). In addition, Sindbis virus is cleared from the CNS of immunodeficient mice by transferred B cells, but not T cells (19), and vesicular stomatitis virus is acutely lethal in B cell-deficient mice (48). Collectively, these results suggest that B cells are required for clearance of some primary viral infections, although the mechanisms of B cell activity may differ depending on the pathogen.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, the liver is not inherently resistant to MHV-A59 persistence, and the immune response is implicated to account for the difference observed between the liver and the CNS in the absence of B cells. Interestingly, other viruses that require B cells for clearance, including Sindbis, vesicular stomatitis virus, HSV-1, Semliki Forest virus, and LCMV, also infect the CNS (18,19,(47)(48)(49). The CNS environment may directly favor a dependency on B cells, perhaps by down-regulation of T lymphocyte function.…”
Section: Discussionmentioning
confidence: 99%